Optimization techniques for rehabilitating water distribution networks - Farouk, A M; Romali, N S; Rahman, R A; M A, Seman (IOP Publishing, 2019)
Water sustainability ensures clean and plentiful water for both current and future generations. Water is the core of sustainable development as it is critical for socio-economic development, healthy ecosystems, and for human survival itself. It helps companies address supply and demand issues by using water more efficiently as well as reducing the amount of water needed to manufacture their products. Maintaining water sustainability is difficult because of a high level of non-revenue water (NRW) or water losses in water distribution networks (WDN). While one of the significant causes of NRW in Malaysia is difficulties in rehabilitating WDN, studies on effective approaches for rehabilitating WDN is limited. So, it is essential to understand the optimization techniques for rehabilitating WDN. Hence, this study’s objective is to identify the different optimization techniques for rehabilitating WDN by systematically reviewing the existing literature on WDN rehabilitation. This research contributes to the body of knowledge in providing insights on optimization techniques for WDN rehabilitation, which could help researchers and industry practitioners reduce NRW and achieve water sustainability